2011
DOI: 10.1039/c0gc00919a
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic catalysts for the Fischer–Tropsch reaction

Abstract: This short critical review summarises and analyses the developments in Fischer-Tropsch catalysis using bimetallic alloys. We introduce a simple notation for such catalysts, and monitor the reports of synergistic effects and composition/performance relationships. Special attention is given to CoFe alloys on a variety of supports, and to the effects of catalyst preparation methods and pre-treatment conditions. The key drawbacks in comparing the large amount of data available on Fischer-Tropsch catalysis are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 63 publications
1
68
0
Order By: Relevance
“…This could suggestt hat the alloy adoptsacore-shell-type structuret hat has ah igher Fe content in the shell. [13,14] The relative abundances of the Co-Fe alloy in the reduced bimetallic samples after in situ PXRD experiments were estimated using Rietveld refinement ( Table 2). The relative abundance of the alloy in the samples was noted to increasea st he Fe/Co ratio approached 5:5.…”
Section: Catalyst Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This could suggestt hat the alloy adoptsacore-shell-type structuret hat has ah igher Fe content in the shell. [13,14] The relative abundances of the Co-Fe alloy in the reduced bimetallic samples after in situ PXRD experiments were estimated using Rietveld refinement ( Table 2). The relative abundance of the alloy in the samples was noted to increasea st he Fe/Co ratio approached 5:5.…”
Section: Catalyst Characterisationmentioning
confidence: 99%
“…Several studies have shown that bimetallic Fe-Co systems do not possessa dditive properties related to the constituent monometallic Fe or Co catalysts, but have unique characteristics. [5,[10][11][12][13] Tavasoli et al observed increased alcohol selectivity from bimetallic Fe-Co/carbon nanotubes (CNTs) catalystsc ompared to that of monometallic Co or Fe, which wasa ttributed to the formationo faC o-Fe alloy. [10] Duvenhage and Covillei nvestigated the effect of the metal precursor used to prepare supported bimetallic catalysts and compared metal nitrates with metal carbonyl complexes as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The promoting effect of adding a second element is often ascribed to effects related to surface structure (ensemble effects) or surface electronic properties (ligand effects). As elegantly described by Liu and Nørskov, [15] these effects can be explained in a quantitative manner by the following example.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Recent advances include synthesis of hybrid structures such as bimetallic nanoparticles and alloys. Interesting properties can arise in bimetallic structures through synergistic effects of their components (Baber et al 2010;Calderone et al 2011;Wang et al 2011). Bimetallic alloys such as Cu-Pd and Ag-Pd have been used as electrocatalysts for the oxygen reduction reaction and for hydrogen purification (Piper 1966;Milhano and Pletcher 2008;Tang et al 2011).…”
Section: Introductionmentioning
confidence: 99%